EEffectiveness of didactic strategies used to promote the achievement of the same curricular objective in the Escuela de Secretariado Profesional: students’ perception - Cordero, Norieth Guillén (2019)
The Office Procedures course of the Escuela de Secretariado Profesional from Universidad Nacional covers topics related to the appropriate management of administrative activities in the modern office. It has a methodology focused on the theoretical analysis of the contents and the constant practice through dramas, simulations, demonstrations, visits to institutions, among others, in order to promote the familiarization of students with the secretarial and administrative techniques of public and private organizations. This article allows knowing the students’ perception about the effectiveness of the different didactic strategies used to propitiate the achievement of the samecurricular objective throughout three years, 2017, 2018 and 2019, as well as the advantages and disadvantages of each one of the strategies.